2014
DOI: 10.1039/c4cp00493k
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-evolving complex of photosystem II: correlating structure with spectroscopy

Abstract: Water oxidation at the oxygen-evolving complex (OEC) of photosystem II (PSII) involves multiple redox states called Sn states (n = 0-4). The S1 → S2 redox transition of the OEC has been studied extensively using various forms of spectroscopy, including electron paramagnetic resonance (EPR) and Fourier transform infrared (FTIR) spectroscopy. In the S2 state, two isomers of the OEC are observed by EPR: a ST = 1/2 form and a ST = 5/2 form. DFT-based structural models of the OEC have been proposed for the two spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 75 publications
(165 reference statements)
5
92
1
Order By: Relevance
“…The altered location of W5 upon Ca 2+ /Sr 2+ substitution might therefore be responsible for the 3-or 4-fold increase in the exchange rate of "slow" substrate water with bulk water when Sr 2+ is used to reconstitute Ca 2+ -depleted PSII 37 and for the reported differences in 2D hyperfine sublevel correlation (HYSCORE) spectra. 38,39 The new positions of W3 and W5 in Sr 2+ -substituted PSII also affect the hydrogen-bond network that connects the OEC to Y Z (reviewed in ref 40), which may account for the slower reduction of Y Z · in all S states, 41 and especially in S 3 . 42 The observed shift in the W3 position is also consistent with a recent DFT model of the Sr 2+ -OEC structure, optimized in the Mn 4 [III,III,III,III] state, 43 although our DFT-QM/MM analysis suggests that the OEC S −1 state is Mn 4 [III,IV,III,II] (Tables S1 and S2).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The altered location of W5 upon Ca 2+ /Sr 2+ substitution might therefore be responsible for the 3-or 4-fold increase in the exchange rate of "slow" substrate water with bulk water when Sr 2+ is used to reconstitute Ca 2+ -depleted PSII 37 and for the reported differences in 2D hyperfine sublevel correlation (HYSCORE) spectra. 38,39 The new positions of W3 and W5 in Sr 2+ -substituted PSII also affect the hydrogen-bond network that connects the OEC to Y Z (reviewed in ref 40), which may account for the slower reduction of Y Z · in all S states, 41 and especially in S 3 . 42 The observed shift in the W3 position is also consistent with a recent DFT model of the Sr 2+ -OEC structure, optimized in the Mn 4 [III,III,III,III] state, 43 although our DFT-QM/MM analysis suggests that the OEC S −1 state is Mn 4 [III,IV,III,II] (Tables S1 and S2).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…As recently reviewed by Pokhrel and Brudvig, the specific hydrogen-bonding network around the OEC strongly affects which S 2 isomer is favored [29]. In PSII samples from higher plants with sucrose as a cryoprotectant, both isomers are present, but for wild-type cyanobacteria, only the S = 1/2 S 2 state is observed [29]. However, for point mutants in Synechocystis sp.…”
Section: Equilibrium Between S 2 Isomersmentioning
confidence: 90%
“…As the fundamental process of water oxidation is assumed to remain unchanged over evolution, analyzing the basis and importance of the surrounding amino-acid residues is key to understanding the mechanism of water oxidation in greater depth. Previous studies have shown that the equilibrium between the two S 2 -state isomers can be affected by a number of different factors such as temperature and small molecules like acetate, fluoride, and nitrite (8,9). All of these factors affect the hydrogen-bonding network surrounding the OEC, thereby stabilizing one of the two isomers.…”
Section: Introductionmentioning
confidence: 99%
“…EPR studies of the S 2 state in PSII from spinach reveal two distinct spin isomers corresponding to S = 1/2 (g = 2) and S = 5/2 (g = 4.1) states that exist in equilibrium with each other (6)(7)(8). In cyanobacterial PSII, however, the S 2 -state EPR spectrum exhibits only the S = 1/2 spin isomer (8). This indicates that even though the core of the OEC is highly conserved there are differences in the surrounding hydrogen-bonding network that affect the equilibrium between these two spin isomers.…”
Section: Introductionmentioning
confidence: 99%